Motorcycle Accident Detection Using Gyroscope, Pulse Sensor, and Global Positioning System Based on Internet of Things with WhatsApp Application - Muhammad, Rafidal; Jonatan, Mario; Cindy Capella, Ayumi; Kurnia, Fajar; Hadary, Ferry (Emitor: Jurnal Teknik Elektro, 2025)
Traffic accidents are one of the leading causes of death in Indonesia. In 2022, there were 94,617 traffic accident cases recorded across the country, resulting in 28,131 fatalities. Motorcycles were involved in 73% of these cases. To reduce the number of motor vehicle accident fatalities, a detection system is needed that can provide real-time accident alerts, location data, and victim health information from distances. The design of this system includes an accident detection device placed on the vehicle and a heart rate detection device in the form of gloves. The accident detection system uses an ESP32 microcontroller, a Gyro MPU6050 sensor, and a GPS NEO6MV2 sensor. It detects accidents based on tilt data and sudden braking. Accident information is sent via WhatsApp chatbot, including the accident location coordinates. Tests showed an average tilt reading difference of 1.34°, an accelerometer reading of 1.89 m/s², and GPS coordinates with an 8.2-meter range. The heart rate detection system uses an ESP32 microcontroller and a MAX30102 heart rate sensor. It sends alerts via WhatsApp chatbot when the user’s heart rate is abnormal. Tests showed an average heart rate reading difference of 11.75 bpm